2023
DOI: 10.1093/jas/skad342
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutrient restriction during late gestation reduces vigor and alters blood chemistry and hematology in neonatal beef calves

Lindsey G Wichman,
Colby A Redifer,
Allison M Meyer

Abstract: Fall-calving primiparous beef females [body weight: 451 ± 28 (SD) kg; body condition score: 5.4 ± 0.7] were individually-fed either 100% (control; CON; n = 13) or 70% (nutrient restricted; NR; n = 13) of metabolizable energy and metabolizable protein requirements for maintenance, pregnancy, and growth from day 160 of gestation to parturition. Calves were reared naturally by their dams and monitored for latency times from birth to first sternal recumbency, attempt to stand, and stand; vigor scores were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…We reported that calf BW and size at birth were not affected by late gestational nutrient restriction ( Redifer et al, 2023 ), but fetal growth is not necessarily indicative of fetal development. Late gestational nutrient restriction resulted in less vigorous calves with more indicators of stress and less red blood cells over the first 48 h of life ( Wichman et al, 2023 ). Calves born to nutrient restricted dams had greater serum immunoglobulin concentrations at 48 h of age, but calves born to dams on both late gestational nutritional planes achieved successful transfer of passive immunity ( Wichman et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We reported that calf BW and size at birth were not affected by late gestational nutrient restriction ( Redifer et al, 2023 ), but fetal growth is not necessarily indicative of fetal development. Late gestational nutrient restriction resulted in less vigorous calves with more indicators of stress and less red blood cells over the first 48 h of life ( Wichman et al, 2023 ). Calves born to nutrient restricted dams had greater serum immunoglobulin concentrations at 48 h of age, but calves born to dams on both late gestational nutritional planes achieved successful transfer of passive immunity ( Wichman et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…We reported that neonatal circulating glucose, urea N, triglycerides, and NEFA during the first 2 d of age were not affected by late gestational nutritional plane ( Wichman et al, 2023 ). Despite the large discrepancy in milk nutrients available ( Redifer et al, 2024 ), calf metabolic status pre-weaning was also minimally affected by late gestational nutritional plane.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations